Redesign Hotel Resort with Regionalism Architecture Approach In Lumban Pea Integrated Tourism Area Development Masterplan - Devin Defriza Harisdani; Arifanda Berkat Simalango (International Journal of Architecture and Urbanism, 2023)
Lumban Pea Integrated Tourism Development Masterplan is one of the tourism development in the Toba Lake Area located in Toba Samosir Regency. In this masterplan, there are several tourism facilities, one of which is the hotel. The hotel design still does not show and apply the cultural values/identity of the surrounding environment in its design. The building is designed in a contemporary form that does not contain cultural attractions in the form of mass, facades, or cosmological values so that it is contrary to the development of tourism in the Lake Toba area which is still full of strong traditions. This study aims to improve the hotel design in the Master Plan by redesigning the hotel. The redesign of the hotel has created a resort hotel that is capable of blending contemporary design but also capturing its cultural side well. The redesign stage begins with conducting a survey, collecting data. In addition, the application of the Regionalism Architecture approach is one of the methodologies used to obtain design criteria which include cultural values, ornaments, forms, and other cultural resonances which are then analyzed and applied to the design. The hotel serves as a temporary residence and recreation facility for tourists. The redesign of this hotel by applying regional values to be a means of education and cultural attractions so that the culture is better known to the wider community and not eroded by the times. Besides, the redesign of this hotel can create a new economic center.